Learning Calibratable Policies using Programmatic Style-Consistency - Zhan, Eric; Tseng, Albert; Yue, Yisong; Swaminathan, Adith; Hausknecht, Matthew (2020 International Conference on Machine Learning, 2020)
We study the problem of controllable generation of long-term sequential behaviors. Solutions to this important problem would enable many applications, such as calibrating behaviors of AI agents in games or predicting player trajectories in sports. In contrast to the well-studied areas of controllable generation of images, text, and speech, there are two questions that pose significant challenges when generating long-term behaviors: how should we specify the factors of variation to control, and how can we ensure that the generated temporal behavior faithfully demonstrates diverse styles? In this paper, we leverage large amounts of raw behavioral data to learn policies that can be calibrated to generate a diverse range of behavior styles (e.g., aggressive versus passive play in sports). Inspired by recent work on leveraging programmatic labeling functions, we present a novel framework that combines imitation learning with data programming to learn style-calibratable policies. Our primary technical contribution is a formal notion of style-consistency as a learning objective, and its integration with conventional imitation learning approaches. We evaluate our framework using demonstrations from professional basketball players and agents in the MuJoCo physics environment, and show that our learned policies can be calibrated to generate interesting behavior styles in both domains.